Development Of Sexual Orientation Scale. A Study On Gay And Lesbian Behaviour From Malaysian Perspective - Roslee Ahmad; Hizral Tazzif Hisham; Lokman Mohd Tahir; Nasir Yusoff; Rahmiwati Marsinun (ResearchTrentz, 2024)
Indexed by SCOPUS/ERA